Does Isometric Handgrip Exercise Really Has Effect on Blood Pressure Changes and Life Quality in People with Hypertension? - Dwi Prihatin Era; Novalinna Appleangeline Rompis; Frana Andrianur (Journal of Social Research, 2022)
In 2020, around 1.56 billion people worldwide were estimated to suffer from hypertension, making it one of the leading causes of death across the globe. The purpose of this research was to examine the impact that isometric handgrip training has on changes in blood pressure as well as the quality of life of people who have hypertension. This research used a quasi-experimental approach with a control group that had different characteristics before and after the tests. The hypothesis test carried out by the intervention group produced p-values that were less than 0.05 for the measures of systolic and diastolic blood pressure as well as quality of life. At the time of the pre-test, the independent statistical analysis of systolic blood pressure, diastolic blood pressure, and quality of life scores for both the intervention group and the control group produced p-values that were greater than 0.05. The p-values for systolic, diastolic, and quality of life scores between the intervention group and the control group at the time of the post-test were 0.013, 0.003, and 0.051, respectively. There were significant differences in the average blood pressure and quality of life scores before and after the intervention of isometric handgrip exercises in the intervention group, whereas there was no difference in the control group. The intervention group consisted of people who did the exercises.